The Effectiveness of E-Comic Utilization as a Learning Media for Tsunami Disaster Mitigation at SMA 1 Pertiwi Padang City - Indriana, Indriana; Umar, Iswandi; Nofrion, Nofrion; Novio, Rery (Journal Of Education And Teaching Learning (JETL), 2024)
Learning in the 21st century is different from learning in the past. Technological advances are growing rapidly in various areas of life, including education. With this change, it gives hope to be able to realize the nation's ideals (BNSP, 2010). The aim of this research is to see the effectiveness of using E-Comic in learning disaster mitigation material in classes XI IPS 1 and XI IPS II. The results of this research obtained an experimental pre-test score of 53.40, a post-test score of 87.10, while the control class had a pre-test score of 51.87 and a post-test score of 61.53. There was a significant increase in the Pre-Test and Posttest of the Control Experiment Class. This shows that E-Comic media can be used by educators as a learning medium in the process of learning activities at school to improve learning outcomes, increase student understanding and also be able to reduce student boredom if they only use the lecture method. Based on the response from educators, the E-Comic media developed in this research responded very well.